Development and assessment of a new cage‐like particle adjuvant. (30th June 2017) - Bertona, Daiana; Pujato, Nazarena; Bontempi, Iván; Gonzalez, Verónica; Cabrera, Gabriel; Gugliotta, Luis; Hozbor, Daniela; Nicastro, Alcides; Calvinho, Luis; Marcipar, Iván Sergio
Abstract: Objectives: To obtain and assess stable cage‐like particles with low surface charge density, which can be prepared using a standardized, economic and scalable method. Methods: To form these nanoparticles, the lipid composition and proportion as well the method were modified in relation to cage‐like particles previously described elsewhere. Bovine albumin was used to compare ISPA performance with that of other adjuvants in mice and to assess stability. Adjuvant efficacy was analysed using a mouse model of Trypanosoma cruzi infection, which shows protection against an intracellular infection that needs a strong cellular response. Key findings: The new particles were better in terms of level, kinetics and profile of humoral responses than Freund Adjuvant, aluminium hydroxide and Montanide TM ISA 206; they also tended to improve ISCOMATRIX ™ performance. Particle size and adjuvant performance were conserved during the 6‐month period assessed after preparation. In the model of Trypanosoma cruzi infection, mice immunized with ISPA and trans‐sialidase developed high protection. Conclusions: The obtained nanoparticles were stable and outperformed the other assessed adjuvants in joining together the capacity of most adjuvants to enhance the immune response against specific antigen, to reduce the number of doses, to homogenize the response between individuals and to reach a balanced TH1/TH2 response.